If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(6v + 11) = sqrt(9v + -2) Reorder the terms: qrst(11 + 6v) = sqrt(9v + -2) (11 * qrst + 6v * qrst) = sqrt(9v + -2) (11qrst + 6qrstv) = sqrt(9v + -2) Reorder the terms: 11qrst + 6qrstv = qrst(-2 + 9v) 11qrst + 6qrstv = (-2 * qrst + 9v * qrst) 11qrst + 6qrstv = (-2qrst + 9qrstv) Solving 11qrst + 6qrstv = -2qrst + 9qrstv Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '2qrst' to each side of the equation. 11qrst + 2qrst + 6qrstv = -2qrst + 2qrst + 9qrstv Combine like terms: 11qrst + 2qrst = 13qrst 13qrst + 6qrstv = -2qrst + 2qrst + 9qrstv Combine like terms: -2qrst + 2qrst = 0 13qrst + 6qrstv = 0 + 9qrstv 13qrst + 6qrstv = 9qrstv Add '-9qrstv' to each side of the equation. 13qrst + 6qrstv + -9qrstv = 9qrstv + -9qrstv Combine like terms: 6qrstv + -9qrstv = -3qrstv 13qrst + -3qrstv = 9qrstv + -9qrstv Combine like terms: 9qrstv + -9qrstv = 0 13qrst + -3qrstv = 0 Factor out the Greatest Common Factor (GCF), 'qrst'. qrst(13 + -3v) = 0Subproblem 1
Set the factor 'qrst' equal to zero and attempt to solve: Simplifying qrst = 0 Solving qrst = 0 Move all terms containing q to the left, all other terms to the right. Simplifying qrst = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(13 + -3v)' equal to zero and attempt to solve: Simplifying 13 + -3v = 0 Solving 13 + -3v = 0 Move all terms containing q to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -3v = 0 + -13 Combine like terms: 13 + -13 = 0 0 + -3v = 0 + -13 -3v = 0 + -13 Combine like terms: 0 + -13 = -13 -3v = -13 Add '3v' to each side of the equation. -3v + 3v = -13 + 3v Combine like terms: -3v + 3v = 0 0 = -13 + 3v Simplifying 0 = -13 + 3v The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 2x-2x+4=7 | | x+265-25=325 | | 7x-92+3x-8=90 | | 8x+37=77 | | 3x(x-4)-2x(x+5)= | | 7x-74+6x-83=90 | | 125000=7x-x | | 8x+86+3x+72=180 | | 4=2(2b+1) | | 15/x=30/7 | | -1*4=a | | -4+3=a | | (9+6i)(7+i)= | | -18+-7+-18+-7=a | | 1/2×-3/5=2/5 | | -10x-3(8+8x)=-6(x-4) | | 4=(2b+1)-60 | | 5x-3(1/2x-1)=-11 | | 3*-4+5=a | | -10-3(8+8x)=-6(x-4) | | 4*-4-2=a | | -6-12/(-3) | | -6(6x+6)-5=1+6x | | -6(1-5a)=-6a+30 | | -45-14= | | 8+7(1+2m)=57 | | 6y+5=-7y+8 | | 7+0.5= | | 6(1-7x)=48 | | 0.2456-a+0.266667=b-a | | 7.4x-5=6.4x | | 5x-3=8x-24 |